Pathogenesis of Periodontal Diseases Biological Concepts for Clinicians (Springer International Publishing, 2018)
This book aims to provide clinicians with a refined understanding of the biology that underlies periodontal diseases, thereby offering a sound basis for improved clinical decision making with regard to prevention strategies, diagnosis, and therapy. All significant aspects of periodontal pathogenesis are covered, including the roles played by the oral microbiome and biofilms, bacterial virulence factors, cells of the immune system, matrix metalloproteinases, proinflammatory and osteolytic cytokines, genetic factors, and antimicrobial peptides. Periodontal diseases are among the most common infectious diseases in humans, and the primary cause of tooth loss in adults. The functional and esthetic problems associated with these diseases compromise quality of life, and their treatment imposes large financial burdens on national health systems and private patients. Up-to-date knowledge of periodontal pathogenesis is therefore essential for the contemporary clinician. This book, written by experts from Europe and the Americas, delivers such knowledge in an accessible, clinician-friendly way.